CHILDREN'S EDUCATION IN ISLAMIC PERSPECTIVE - Salsabila Matondang; M. Ilyasa Ramadhan (Proceeding International Seminar of Islamic Studies, 2022)
In the view of Islam,children are one of Gods great gifts which are only given to couples who are trusted to carry out their duties as parents. On that basis,children are a mandate from God for parents.The first and the prime education for children in Islam is the Islamic family education.Islamic education in the family that has been implemented in accordance with Islamic guidance basically intends to educate children to become human beings who believe and fear God Almighty,have noble character that includes ethics,morals,character,spirituality or understanding and knowledge of religious values in everyday life.Keywords: Child Education,Family,and Islam